Wear-resistant and corrosion-resistant metal material, preparation method thereof and metal material product

The integration of a ceramic reinforcement phase into an iron-based alloy addresses the scratch and corrosion issues of stainless steel, providing enhanced resistance to friction and impact, ensuring durability and corrosion resistance in demanding conditions.

CN119194304APending Publication Date: 2024-12-27HANGZHOU ROBAM APPLIANCES CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411507260.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Stainless steel surfaces are prone to scratches and reduced corrosion resistance when rubbed or hit by sharp or hard objects, leading to aesthetic issues and increased susceptibility to corrosion, especially during processing and use in specific environments.

Method used

A wear-resistant and corrosion-resistant metal material is developed by incorporating a ceramic reinforcement phase, such as tantalum carbide, into an iron-based alloy, optimizing the alloy composition to enhance resistance to friction and impact, and forming a metallurgical bond with the iron matrix for improved hardness and load transfer efficiency.

Benefits of technology

The metal material exhibits enhanced scratch resistance and corrosion resistance, maintaining appearance and performance in challenging environments, with improved Vickers hardness and reduced risk of coating failure.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of alloy materials, and particularly relates to a wear-resistant and corrosion-resistant metal material, a preparation method thereof and a metal material product, the metal material comprises an iron-based alloy and a ceramic reinforced phase, the iron-based alloy comprises the following main components: 13-25 wt% of Cr, 3-5 wt% of Ni, 0.5-1.5 wt% of Ti, 1-3 wt% of Nb, 0.01-0.1 wt% of N, 0.01-1 wt% of C, 1-2 wt% of Mn, 0.01-1 wt% of Si, less than 0.04 wt% of P, less than 0.02 wt% of S, and the balance of iron and some inevitable impurities. Compared with the prior art, the metal material provided by the invention has a better anti-scraping effect, especially for scraping and collision of sharp or hard objects and the like, and meanwhile, the metal material has more excellent corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of alloy materials, and in particular relates to a wear-resistant and corrosion-resistant metal material, a preparation method thereof, and a metal material product. Background Art

[0002] Stainless steel is widely used in the kitchen appliance industry due to its good corrosion resistance, machinability, and beautiful appearance. In order to improve the surface properties of stainless steel, such as corrosion resistance and wear resistance, a passivation film is usually formed on the surface of stainless steel. Although the passivation film has a certain resistance to corrosion and wear, it is still very easy to be damaged if it is rubbed or hit by sharp or hard objects in the use environment, resulting in scratches on the surface. Moreover, stainless steel is also prone to scratches during processing, such as cutting, welding, and grinding, especially when proper protective measures are not taken. The presence of scratches not only affects the appearance of stainless steel, but may also become the starting point of corrosion, because the passivation film at the scratch is destroyed, making the steel more susceptible to erosion by corrosive media, making the corrosion resistance of traditional stainless steel unable to meet the use requirements in certain specific application environments. Summary of the invention

[0003] In order to solve the above-mentioned problems existing in stainless steel, the present invention provides a wear-resistant and corrosion-resistant metal material, a preparation method thereof and a metal material product, which optimizes the formula of the metal material, can not only ensure excellent corrosion resistance and wear resistance, but also have better resistance to friction and impact of sharp or hard objects without causing scratches.

[0004] A first aspect of the present invention provides a wear-resistant and corrosion-resistant metal material, comprising an iron-based alloy and a ceramic reinforcement phase, wherein the main components of the iron-based alloy are 13-25wt% Cr, 3-5wt% Ni, 0.5-1.5wt% Ti, 1-3wt% Nb, 0.01-0.1wt% N, 0.01-1wt% C, 1-2wt% Mn, 0.01-1wt% Si, P < 0.04wt%, S < 0.02wt%, and the remainder is iron and some inevitable impurities.

[0005] In the scheme of the present invention, the rigidity of the metal material is improved by the ceramic reinforcement phase to resist adverse friction and impact, so as to reduce the risk of scratches. In the prior art, a corresponding layer is formed on the surface of a substrate formed on the surface of a metal material through a ceramic reinforcement phase, that is, the ceramic reinforcement phase is formed on the surface of the substrate. The wear-resistant layer formed in this way not only has the risk of the coating falling off after a period of use, but the spraying process of the coating will increase the production process and cause environmental pollution.

[0006] Therefore, the present invention attempts to directly add ceramic reinforcement phase to the iron-based alloy. And by optimizing the iron-based alloy formula, the nickel content is reduced compared to 304 stainless steel. By adding titanium and niobium elements, the alloy is more stable to prevent sensitized intergranular corrosion. On the one hand, N can be used as an austenite forming element and can also improve the creep performance of austenitic stainless steel. The addition of Mn can improve the thermoplasticity of the material and improve the corrosion resistance of the material. The ceramic reinforcement phase has a very high melting point and hardness, can resist the plastic deformation and wear of the material, and protect the iron-based matrix from wear. The mixed powder obtained by the preparation method can improve the dispersion of the reinforcement phase in the iron-based alloy. The reinforcement phase particles and the iron matrix form a metallurgical bond through an in-situ reaction, which can improve the load transfer efficiency of the composite material. The subsequent sintering of the powder can make the product obtain good hardness and wear resistance.

[0007] Preferably, the ceramic reinforcement phase is tantalum carbide. In this solution, tantalum carbide is used as the ceramic reinforcement phase, which has a better mutual cooperation effect with the iron-based alloy in the above solution, giving the material more stable corrosion resistance and excellent Vickers hardness.

[0008] Preferably, in the metal material, the iron-based alloy accounts for 65% to 80% of the total mass of the metal material. The addition ratio of the iron-based alloy to the ceramic reinforcement phase also has a great influence on the final performance of the material. When the addition amount of the iron-based alloy is low, although the corrosion resistance can be guaranteed, the Vickers hardness decreases significantly and cannot resist the scratching of external forces.

[0009] Preferably, the tantalum carbide is formed by mixing tantalum pentoxide and carbon black and sintering the mixture in a vacuum atmosphere.

[0010] Preferably, the molar ratio of tantalum pentoxide to carbon black is 1:4.9 to 1:5.2. During vacuum sintering, controlling the molar ratio of tantalum pentoxide powder to carbon black is more beneficial for the formed tantalum carbide to impart the properties of the metal material of the present invention.

[0011] Preferably, the particle size of the tantalum pentoxide powder and the carbon black powder is 250-350 mesh, and the purity is 96-99%.

[0012] A second aspect of the present invention provides a method for preparing the wear-resistant and corrosion-resistant metal material, comprising the following steps:

[0013] S1. The ceramic reinforcement phase powder is mixed with the iron-based alloy powder, and ball milled under the protection of argon gas in a vacuum environment to obtain a mixed powder;

[0014] S2. annealing the mixed powder at a temperature of 660°C to 770°C for 30 min to 35 min, and cooling to room temperature to obtain a metal material.

[0015] Preferably, in step S1, the mass ratio of stainless steel grinding balls to materials is 30:1 to 35:1.

[0016] Preferably, the ceramic reinforcement phase powder is formed by mixing tantalum pentoxide powder and carbon black powder and sintering the mixture in a vacuum atmosphere.

[0017] A third aspect of the present invention provides a metal product, which is made of the metal material as described above or the metal material obtained by the preparation method as described above.

[0018] By implementing the above technical solution, compared with the prior art, the present invention has the following beneficial effects:

[0019] The metal material provided by the present invention has a better anti-scratch effect, especially against scratches and impacts from sharp or hard objects. At the same time, the metal material has a better corrosion resistance. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0021] Example 1

[0022] This embodiment provides a wear-resistant and corrosion-resistant metal material, which is obtained according to the following method:

[0023] 15wt% Cr, 4wt% Ni, 0.5wt% Ti, 1.2wt% Nb, 0.05wt% N, 0.06wt% C, 1.2wt% Mn, 0.9wt% Si, 0.01wt% P, 0.01wt% S, and the rest is iron, added to a suspension smelting furnace, smelting temperature 1450℃, atomization powder making method to obtain iron-based alloy powder. Tantalum pentoxide powder (particle size 300 mesh, purity 98%) and carbon black powder (particle size 300 mesh, purity 98%) are mixed in a mass ratio of 1:5.0 and sintered in an inert atmosphere at 1500 degrees. The obtained mixed powder and iron-based alloy powder are put into a ball mill, the amount of iron-based alloy powder added is 75% of the total amount of powder, stainless steel balls are added to the ball mill according to a ball-to-material ratio of 35:1, and ball milling is carried out at a speed of 300r / min for 6 hours under the protection of nitrogen atmosphere. The ball-milled powder was annealed in a vacuum furnace at a temperature of 710 degrees for 30 minutes, and then cooled to room temperature to obtain a tantalum carbide-iron-based alloy mixed powder.

[0024] Example 2

[0025] The present embodiment provides a wear-resistant and corrosion-resistant metal material. The only difference from Embodiment 1 is that the composition of the iron-based alloy is different. The iron-based alloy of the present embodiment is: 15wt% Cr, 3wt% Ni, 1.0wt% Ti, 2.0wt% Nb, 0.05wt% N, 0.01wt% C, 1.0wt% Mn, 0.05wt% Si, 0.01wt% P, 0.01wt% S, and the rest is iron.

[0026] Example 3

[0027] The present embodiment provides a wear-resistant and corrosion-resistant metal material. The only difference from Embodiment 1 is that the composition of the iron-based alloy is different. The iron-based alloy of the present embodiment is: 20wt% Cr, 4wt% Ni, 0.5wt% Ti, 1.2wt% Nb, 0.1wt% N, 0.06wt% C, 1.2wt% Mn, 0.9wt% Si, 0.01wt% P, 0.01wt% S, and the rest is iron.

[0028] Example 4

[0029] The present embodiment provides a wear-resistant and corrosion-resistant metal material. The only difference from Embodiment 1 is that the composition of the iron-based alloy is different. The iron-based alloy of the present embodiment is: 13wt% Cr, 5wt% Ni, 1.5wt% Ti, 1.2wt% Nb, 0.05wt% N, 0.06wt% C, 1.2wt% Mn, 0.9wt% Si, 0.01wt% P, 0.01wt% S, and the rest is iron.

[0030] Example 5

[0031] The present embodiment provides a wear-resistant and corrosion-resistant metal material. The only difference from Embodiment 1 is that the composition of the iron-based alloy is different. The iron-based alloy of the present embodiment is: 15wt% Cr, 4wt% Ni, 1.5wt% Ti, 1.2wt% Nb, 0.01wt% N, 0.02wt% C, 2.0wt% Mn, 0.9wt% Si, 0.01wt% P, 0.01wt% S, and the rest is iron.

[0032] Example 6

[0033] This embodiment provides a wear-resistant and corrosion-resistant metal material. The only difference from Embodiment 1 is that the amount of iron-based alloy powder added is 80% of the total amount of powder.

[0034] Example 7

[0035] This embodiment provides a wear-resistant and corrosion-resistant metal material. The only difference from Embodiment 1 is that the amount of iron-based alloy powder added is 65% of the total amount of powder.

[0036] Example 8

[0037] This embodiment provides a wear-resistant and corrosion-resistant metal material. The only difference from Embodiment 1 is that the amount of iron-based alloy powder added is 70% of the total amount of powder.

[0038] Example 9

[0039] This embodiment provides a wear-resistant and corrosion-resistant metal material. The only difference from Embodiment 1 is that the mass ratio of tantalum pentoxide powder and carbon black powder added is 1:5.3.

[0040] Example 10

[0041] This embodiment provides a wear-resistant and corrosion-resistant metal material. The only difference from Embodiment 1 is that the mass ratio of stainless steel grinding balls to materials in the ball mill is 30:1.

[0042] Embodiment 11

[0043] This embodiment provides a wear-resistant and corrosion-resistant metal material. The only difference from Embodiment 1 is that the annealing temperature is 700° C. and the heat preservation time is 30 minutes.

[0044] Example 12

[0045] This embodiment provides a wear-resistant and corrosion-resistant metal material. The only difference from Embodiment 1 is that the annealing temperature is 680° C. and the heat preservation time is 35 minutes.

[0046] Example 13

[0047] This embodiment provides a wear-resistant and corrosion-resistant metal material. The only difference from Embodiment 1 is that the mass ratio of stainless steel grinding balls to materials in the ball mill is 40:1.

[0048] Embodiment 14

[0049] This embodiment provides a wear-resistant and corrosion-resistant metal material. The only difference from Embodiment 1 is that the amount of iron-based alloy powder added is 85% of the total amount of powder.

[0050] Embodiment 15

[0051] This embodiment provides a wear-resistant and corrosion-resistant metal material. The only difference from Embodiment 1 is that the amount of iron-based alloy powder added is 55% of the total amount of powder.

[0052] Comparative Example 1

[0053] This comparative example provides a wear-resistant and corrosion-resistant metal material. The only difference from Example 1 is that the composition of the iron-based alloy is different. This comparative example uses 304 stainless steel (20wt% Cr, 8wt% Ni, 0.1wt% N, 0.08wt% C, 2wt% Mn, 0.75wt% Si, 0.045wt% P, 0.03wt% S, and the balance is iron).

[0054] Comparative Example 2

[0055] This comparative example provides a wear-resistant and corrosion-resistant metal material. The only difference from Example 1 is that the composition of the iron-based alloy is different. The composition of the iron-based alloy in this comparative example is: 15wt% Cr, 4wt% Ni, 0.1wt% Ti, 0.1wt% Nb, 0.05wt% N, 0.06wt% C, 1.2wt% Mn, 0.9wt% Si, 0.01wt% P, 0.01wt% S, and the balance is iron.

[0056] Comparative Example 3

[0057] This comparative example provides a wear-resistant and corrosion-resistant metal material. The only difference from Example 1 is that the composition of the iron-based alloy is different. The composition of the iron-based alloy in this comparative example is: 15wt% Cr, 4wt% Ni, 0.5wt% Ti, 1.2wt% Nb, 0wt% N, 0.06wt% C, 0.1wt% Mn, 0.9wt% Si, 0.01wt% P, 0.01wt% S, and the balance is iron.

[0058] The examples and comparative examples were tested for acid resistance, alkali resistance and Vickers hardness. The test methods are as follows. The test results are shown in Table 1.

[0059] Alkali resistance test: Place the sample in 15% sodium hydroxide solution, soak for 72 hours at room temperature, and observe the surface changes. Acid resistance test: The sample is subjected to AASS test, and the surface changes are observed after 72 hours.

[0060] Vickers hardness: Vickers hardness is measured using a 432SVD micro-Vickers hardness tester. The hardness test process is carried out in accordance with the standard "GB / T4340.1-2009 Vickers hardness test for metal materials".

[0061] Table 1

[0062] sample Alkali resistance Acid resistance test Vickers hardness Example 1 No surface changes No surface changes 425 Example 2 No surface changes No surface changes 423 Example 3 No surface changes No surface changes 427 Example 4 No surface changes No surface changes 424 Example 5 No surface changes No surface changes 421 Example 6 No surface changes No surface changes 420 Example 7 No surface changes No surface changes 425 Example 8 No surface changes No surface changes 422 Example 9 No surface changes No surface changes 410 Example 10 No surface changes No surface changes 424 Embodiment 11 No surface changes No surface changes 423 Example 12 No surface changes No surface changes 421 Example 13 No surface changes No surface changes 418 Embodiment 14 No surface changes No surface changes 410 Embodiment 15 No surface changes No surface changes 435 Comparative Example 1 Corrosion marks on the surface Corrosion marks on the surface 414 Comparative Example 2 Corrosion marks on the surface Corrosion marks on the surface 420 Comparative Example 3 Corrosion marks on the surface Corrosion marks on the surface 421

[0063] From the test results shown in Table 1, the metal material of the present invention has excellent acid and alkali resistance, while in Comparative Example 1, the iron-based alloy uses 304 stainless steel, and its corrosion resistance is worse than that of the specific iron-based alloy used in Example 1 of the present invention. In addition, the Vickers hardness is also reduced. The iron-based alloy in Comparative Example 2 reduces the content of Ti and Nb, and the results show that the corrosion resistance of the sample is reduced. The iron-based alloy in Comparative Example 3 does not add N, and the Mn content is reduced at the same time. The results show that the corrosion resistance of the sample is also reduced.

Claims

1. A wear-resistant and corrosion-resistant metal material, comprising an iron-based alloy and a ceramic reinforcement phase, characterized in that: The main components of the iron-based alloy are 13-25wt% Cr, 3-5wt% Ni, 0.5-1.5wt% Ti, 1-3wt% Nb, 0.01-0.1wt% N, 0.01-1wt% C, 1-2wt% Mn, 0.01-1wt% Si, P<0.04wt%, S<0.02wt%, and the balance is iron and some inevitable impurities.

2. The wear-resistant and corrosion-resistant metal material according to claim 1, characterized in that: The ceramic reinforcement phase is tantalum carbide.

3. The wear-resistant and corrosion-resistant metal material according to claim 1, characterized in that: In the metal material, the iron-based alloy accounts for 65% to 80% of the total mass of the metal material.

4. The wear-resistant and corrosion-resistant metal material according to claim 2, characterized in that: The tantalum carbide is formed by mixing tantalum pentoxide and carbon black in an inert gas or vacuum environment and then sintering the mixture in a vacuum atmosphere.

5. The wear-resistant and corrosion-resistant metal material according to claim 4, characterized in that: The molar ratio of the tantalum pentoxide to the carbon black is 1:4.9 to 1:5.

2.

6. The wear-resistant and corrosion-resistant metal material according to claim 5, characterized in that: The particle sizes of the tantalum pentoxide powder and the carbon black powder are 250-350 meshes, and the purity is 96-99%.

7. A method for preparing a wear-resistant and corrosion-resistant metal material according to any one of claims 1 to 6, characterized in that: The steps include: S1. The ceramic reinforcement phase powder is mixed with the iron-based alloy powder, and ball milled under the protection of argon gas in a vacuum environment to obtain a mixed powder; S2. The mixed powder is annealed at a temperature of 660°C to 770°C for 30 min~35min, cool to room temperature to obtain metal material.

8. The method for preparing a wear-resistant and corrosion-resistant metal material according to claim 7, characterized in that: During the ball milling in step S1, the mass ratio of the stainless steel grinding balls to the material is 30:1 to 35:

1.

9. The method for preparing a wear-resistant and corrosion-resistant metal material according to claim 7, characterized in that: The ceramic reinforcement phase powder is formed by mixing tantalum pentoxide and carbon black and sintering the mixture in a vacuum atmosphere.

10. A metal product, made of the metal material according to any one of claims 1 to 6 or made of the metal material obtained by the preparation method according to claims 7 to 9.